The Influence of Human Resources and Infrastructure Competence on the Performance of Licensing Services in the Investment Office and One-Stop Integrated Services of Central Maluku Regency - K.F. Asiqien Karepesina; Normawati Normawati; J.A. Ufie; Hendry Selanno (Syntax Idea)
This study aims to determine the Effect of Human Resources and Infrastructure Competence on the Performance of Licensing Services in the Investment Office and One-Stop Integrated Services of Central Maluku Regency, both partially and simultaneously. This type of research is quantitative research. The respondents in this study were people/business actors who came to the Investment Office and One-Stop Integrated Services of Central Maluku Regency to apply for permits with the number of samples obtained as many as 80 people. Data collection techniques using questionnaires and processed using the SPSS statistical analysis application program. The results showed that partially and simultaneously the competence of Human Resources and infrastructure facilities had a positive and significant effect on the performance of licensing services at the Investment Office and One-Stop Integrated Services of Central Maluku Regency.